2022
DOI: 10.1245/s10434-021-11193-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Utilization and Outcomes of Minimally Invasive Techniques for Gastric Cancer Surgery in the United States

Abstract: Background This study investigated national implementation patterns and perioperative outcomes of minimally invasive gastrectomy (MIG) in gastric cancer surgery in the United States. Methods The National Inpatient Sample (NIS) was queried for patients who underwent elective gastrectomy for gastric cancer from 2008-2018. The MIG versus open gastrectomy approach was correlated with hospital factors, patient characteristics, and complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Patient risk profile as well as institutional practice patterns are known to influence morbidity following surgery as well as expected postoperative length of stay [29,30]. In our analysis, we found several operative and hospital factors to be associated with increased odds of expedited discharge.…”
Section: Plos Onementioning
confidence: 59%
“…Patient risk profile as well as institutional practice patterns are known to influence morbidity following surgery as well as expected postoperative length of stay [29,30]. In our analysis, we found several operative and hospital factors to be associated with increased odds of expedited discharge.…”
Section: Plos Onementioning
confidence: 59%
“…1). While the NSQIP database does not differentiate between hospital demographics, previous studies have shown socioeconomic differences in the utilization of LG could be explained by hospital level factors [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative costs are partially attributable to operative times and surgical equipment, leading to a higher cost attributed to minimally invasive approaches. A national database review from Park et al 53 reported a $4700 higher hospital cost for MIG compared with OG, whereas other studies have indicated that cost increases are more likely associated with RG compared with LG. For example, Lu et al 54 documented total hospital costs of $13,423 for RG compared with $10,165 for LG ( p < .001); but Jin et al 56 calculated a mean difference of $19,141 in perioperative costs between RG and LG.…”
Section: Surgical Approachesmentioning
confidence: 97%
“…51,52 Results are similarly mixed for postoperative mortality; however, overall, RG appears to be noninferior to OG. 49,50 Authors of national database analyses concluded that MIG was associated with improved rates of 30-day 53 and 90-day mortality, 44 but the proportion of MIG cases that were performed robotically is unclear.…”
Section: Isuor Ricgl Fusicfmcamentioning
confidence: 99%